Effects Of Mixed Aqueous-Organic Cosolvents On The Rates Of Cleavage Of N-(2'-Hydroxyphenyl)Phthalimide (1) And N-(2'-Methoxyphenyl)-Phthalimide (2) In Alkaline Media - Ariffin, Azhar; Khan, M.N.; Abdullah, N.; Sim, Y.L. (2007)
The effects of mixed H2O-OCS (where organic cosolvents (OCS) = methanol, ethanol, 1-propanol, 2-propanol, 1,4-dioxan and acetonitrile) on the first-order rate constants, k(obs), for hydrolysis of I at 1.0 X 10(-3) M NaOH and 2 at 2.0 x 10(-3) M NaOH show a nonlinear decrease in k(obs), with increasing contents of OCS. The k(obs), - decreasing sensitivity of mixed H2O - OCS solvents within 5 X% v/v OCS, where X ranges from 50 to 90, is ca 2- to 9-fold larger for hydrolysis of 2 than that of 1. This observed characteristic difference is attributed to the occurrence of different rate laws in these reactions, i.e. rate = k(w) [1(-)][H2O] and rate = k(OH) [2][HO-] in the hydrolyses of 1 and 2, respectively.